2018
DOI: 10.1021/acsanm.8b00392
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Laser Fabrication of Antifouling Silicon-Surface Nanosheet Arrays via Nanoplasmonic Ablative Self-Organization in Liquid CS2 Tracked by a Sulfur Dopant

Abstract: Large-scale surface nanopatterning of a commercial silicon (Si) wafer in the form of regular 1D arrays of high-aspect-ratio vertical nanosheets (NSs) for antifouling and other potential promising optoelectronic, nanophotonic, and sensing applications was performed via multishot picosecond IRlaser ablation under a 5-mm-thick carbon disulfide liquid layer. Specifically, the nanopatterned surface layer demonstrates the broad ultralow mid-IR transmittance and the high content of sulfur, carbon, and even oxygen in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 38 publications
3
40
0
Order By: Relevance
“…Production of hyperdoped Si nanoparticles in colloidal solutions was performed during ablative laser nanopatterning of Si surfaces in carbon disulfide ambient, [ 20 ] in one pass over 10 mm × 10 mm wide areas on a 0.38‐mm thick phosphor‐doped commercial Si(111) wafer (specific resistivity of 4.5 Ω cm) inside a glass beaker with a top 5‐mm thick carbon disulfide (CS 2 ) layer; the ppb‐level phosphor impurity hadn't affected the studies.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Production of hyperdoped Si nanoparticles in colloidal solutions was performed during ablative laser nanopatterning of Si surfaces in carbon disulfide ambient, [ 20 ] in one pass over 10 mm × 10 mm wide areas on a 0.38‐mm thick phosphor‐doped commercial Si(111) wafer (specific resistivity of 4.5 Ω cm) inside a glass beaker with a top 5‐mm thick carbon disulfide (CS 2 ) layer; the ppb‐level phosphor impurity hadn't affected the studies.…”
Section: Methodsmentioning
confidence: 99%
“…The laser exposure was provided at 100‐kHz repetition rate by 300‐fs, IR‐laser pulses focused onto the sample surface into a spot with the 1/e‐radius σ ≈ 15 µm (the peak surface laser fluence F 0 ≈ 0.5 J cm −2 ) with 400 pulses per spot, resulting in visibly black, highly‐ordered nanosheet‐like surface textures (Figures 1a and 2a) described elsewhere. [ 20 ]…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is believed that the biggest obstacle to the application of two-dimensional nanomaterials as ame retardant additives is the high cost and the low yield of the peeled sheet structures [46]. Recently, as the number of publications related to these emerging twodimensional nanomaterials has increased dramatically, a large number of studies on the large-scale production of twodimensional nanosheets have paved the way for ame-retardant applications [47,48]. Yao et al [49] reported a facile and scalable method for the preparation of monolayer and fewlayer of BN, MoS 2 , and graphene using a combination of low-energy ball milling and sonication.…”
Section: Introductionmentioning
confidence: 99%